Handbook of Osteoporosis - Reid, David; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2011)
Handbook of Osteoporosis provides a concise but highly illustrated and essential resource for clinicians in the management of postmenopausal osteoporosis. Opening with overviews of epidemiology, clinical features and pathophysiology, the book then discusses approaches to screening and prevention. Chapters on the assessment of both osteoporosis and risk factors for osteoporotic fracture are followed by discussion of pharmacological and non-pharmacological approaches to the management of osteoporosis. The book concludes with a discussion of the long-term management issues of pain management and optimising compliance. The concise handbook format and ample illustration make Handbook  of Osteoporosis an invaluable reference for primary care physicians, rheumatologists, orthopaedic surgeons, geriatricians, endocrinologists, and nurse specialists who wish to keep up to date in the prevention and management of osteoporosis.
Keywords: Rheumatology; Rheumatology